Assessing symptom improvement in patients with postural orthostatic tachycardia syndrome (POTS) following a 16-week structured exercise programme: a protocol for a randomised cross-over trial in a clinical outpatient setting - Artur Fedorowski; Viktor Hamrefors; Hannes Holm; Isabella Kharraziha; Rafael Zulj (BMJ Open, 2025)
Introduction Exercise training is recommended as a complementary treatment in postural orthostatic tachycardia syndrome (POTS) according to international guidelines. However, less is known regarding how exercise training could successfully be implemented in clinical practice in patients with POTS. Thus, in the current study, we aim to assess the effect of a 16-week tailored exercise training programme in POTS.Methods and analysis A total of 200 patients diagnosed with POTS will be recruited. The study will be conducted as a randomised cross-over study. POTS symptoms will be evaluated using the Malmö POTS Symptom Score, Orthostatic Hypotension Questionnaire and 36-item Short Form Health Survey. Haemodynamic parameters will be evaluated by orthostatic tests and maximum working capacity evaluated by bicycle exercise test. Symptoms, haemodynamic parameters and exercise capacity will be assessed before and after a 16-week training programme.Ethics and dissemination The study was approved by the Swedish ethical review authority (2022-03186-01) and all procedures will be performed in accordance with the Helsinki Declaration. Results will be made available to patients with POTS, healthcare professionals, the funders and other researchers in publicly available (open access) medical journals.Trial registration details NCT05554107, registered on 26 September 2022.